The perceived effect of social media towards adolescenece in their psychological behavior: a case study of the perception of students in Shah Alam towards mental illness. / Rusyaidatul Zhafirah Redza - Redza, Rusyaidatul Zhafirah (2017)
The consumer of media consists of variety of background and ages, adolescence is one of the higher users to be exposed towards media and technologies. Indirectly, this issue could lead towards the changes of psychological behavior among adolescence. The goal of present research is to determine effect of social media towards adolescence in their psychological behavior from the perception of students in Shah Alam towards mental illness. Mental illness is the illness that can spread towards adolescence based from the usage of media such as social media. Stigmatization can be channel using media and society still lack in the knowledge regarding of mental illness. The theory related with this research is User and Gratification Theory (UNG), to relate the consumer dependency on using of media in their daily life and how this theory show consumer have different interpretation from the information they gain trough media. The method used in this research is quantitative method and using Likert Scale to collecting the data from the respondents. This research determined the finding of level of awareness, pressure from peer and stigmatization of media towards the mental illness from the perspective of students in Shah Alam.